The effects of placement method on multilingual learner success in higher education - Key Jr, William (TESOL Journal, 2024)
In the United States, many actors are pushing for the use of grade point average (GPA) as the main placement tool for gatekeeper math and English courses for community college students (Quarles, 2022; Scott-Clayton, 2018; Turk, 2017). One community college system (pseudonymously, SXCC) in a New England state has begun placing students in initial math and English classes based on self-reported GPA. There have been studies on the effects of placement changes of this type (Belfield & Crosta, 2012; Hodara & Cox, 2016; Ngo & Kwon, 2014; Scott-Clayton, 2012). However, studies have not included the effects of these changes on multilingual learners (MLLs).Using a census of every MLL placed in SXCC in the summer and fall of 2020 and the spring of 2021 (N = 12,603), a MANOVA found that MLL students in the SXCC system who were placed using previous placement methods had a higher overall GPA than students placed using self-reported GPA (M = 3.32, SD = 0.740; M = 2.01, SD = 1.27, respectively) and had higher satisfactory academic progress (SAP) (M = 102.98, SD = 51.52; M = 57.66, SD = 55.53, respectively), and took longer to enroll in English 101 (M = 5.11, SD = 3.55; M = 2.36, SD = 1.76, respectively).
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/tesj.835
Keywords: dept.edu; peer-reviewed

Take me to Nana's house - Mansfield, Christian (Independently published, 2023)
A young boy remembers fond childhood memories at his grandmother's house, where he learned the small things in life that truly mattered.
Keywords: SCSU-student; dept.edu

Mathematical strategies and emergence of socially mediated metacognition within a multi-touch Dynamic Geometry Environment - Hegedus, S.J.; Otálora, Y. (Educational Studies in Mathematics, 2022)
Our research aimed to investigate the potential learning benefits to young children of implementing digital interactive multimodal technologies that provide both visual and haptic experiences in elementary mathematics classrooms. We studied the ways in which fourth-grade students collaboratively create collective strategies for solving mathematical problems utilizing dynamic geometry software with multi-touch interfaces, a combination we call a multi-touch Dynamic Geometry Environment. We examine in-depth two case studies each illustrating how mathematical strategies, collaboration, and socially mediated metacognition emerge in the small groups of children while working on an activity using the Geometer’s Sketchpad® on the iPad to make sense of an intuitive idea of covariation. We found that children’s interactions with their peers, the interviewer, and the mDGE favored the emergence of varied collaborative behaviors and socially mediated metacognitive processes that fostered the co-construction and development of mathematical strategies over a short period of time. © 2022, The Author(s), under exclusive licence to Springer Nature B.V.
1 citations (Crossref) [2023-10-31]
Keywords: Collaboration; Dynamic geometry software; Mathematical strategies; Multi-touch; Socially mediated metacognition; Young children; dept.edu; peer-reviewed

High school mathematics teachers’ discernment of invariant properties in a dynamic geometry environment - Nagar, G.G.; Hegedus, S.; Orrill, C.H. (Educational Studies in Mathematics, 2022)
Variance and invariance are two powerful mathematical ideas to support geometrical and spatial thinking, yet there is limited research about teachers’ knowledge of variance and invariance. In this paper, we examined how high school teachers deal with the task of looking for invariant properties in a dynamic geometry environment (DGE) setting. Specifically, we investigated if they even attend to invariant properties; what invariant properties they discern and discuss; and how DGE can support such discernment. Our analysis found that teachers tend to discern and discuss invariant properties mainly when they were probed to consider invariance. We also found four categories of invariant properties that seem to be important for a robust and rich understanding of geometric objects in the context of invariance and DGE. The use of DGE allowed teachers to see and interact with invariant properties, thus suggesting that accessing geometry dynamically may have structural affordances especially when exploring invariance. Teachers were able to enact different DGE movements to discern and discuss invariant properties, as well as to reason with and about them. We also saw that teachers’ backgrounds and past experiences can play an important role in their descriptions of invariant properties. Possible future research directions and implications to teacher education are discussed. © 2022, The Author(s), under exclusive licence to Springer Nature B.V.
4 citations (Crossref) [2023-10-31]
Keywords: Digital technologies; Discernment of invariant properties; Dynamic geometry environment; Geometric reasoning; Geometrical and spatial perception; Variance and invariance; dept.edu; peer-reviewed